2015
DOI: 10.1038/aps.2015.85
|View full text |Cite
|
Sign up to set email alerts
|

Aconine inhibits RANKL-induced osteoclast differentiation in RAW264.7 cells by suppressing NF-κB and NFATc1 activation and DC-STAMP expression

Abstract: Aim: Aconiti Lateralis Radix Preparata is a traditional Chinese medicine used to treat chronic arthritis and is highly effective against rheumatoid arthritis. However, the effects of aconine, a derivative of aconitum alkaloids, on osteoclasts, which can absorb bone, remain unknown. Here, we investigated the effects of aconine on osteoclast differentiation and bone resorption in vitro. Methods: The viability of mouse leukemic monocyte/macrophage cell line RaW264.7 was measured using CCK-8 assays. osteoclast dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 28 publications
0
80
0
Order By: Relevance
“…Osteoclasts are differentiated from hematopoietic myeloid precursor cells of monocyte/macrophage lineage . The murine macrophage cell line RAW264.7 cells are commonly used as osteoclast precursors; these cells have become a valuable tool to study osteoclast differentiation . RANKL induces osteoclast differentiation, function, and survival of cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclasts are differentiated from hematopoietic myeloid precursor cells of monocyte/macrophage lineage . The murine macrophage cell line RAW264.7 cells are commonly used as osteoclast precursors; these cells have become a valuable tool to study osteoclast differentiation . RANKL induces osteoclast differentiation, function, and survival of cells .…”
Section: Discussionmentioning
confidence: 99%
“…24 The murine macrophage cell line RAW264.7 cells are commonly used as osteoclast precursors; these cells have become a valuable tool to study osteoclast differentiation. 25,26 RANKL induces osteoclast differentiation, function, and survival of cells. 27 In our study, we found that omega-3 plus aspirin markedly attenuated the number of RANKL-stimulated TRAP (+) multinucleated cells in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, 10 μL of CCK‐8 solution was added to each well of cells. After further incubation of the plate in an incubator at 37°C for 4 hours, the absorbance at 450 nm was measured using a microplate reader (Perkin Elmar) and then the cell viability was analysed according to formula as described …”
Section: Methodsmentioning
confidence: 99%
“…RA belongs to the category of Bi Zheng in traditional Chinese medicine theory. A variety of traditional Chinese medicines resistant to Bi Zheng show the potentials to treat RA (Gao, Feng, Zhang, Wang, & Cui, ; Zeng et al, ). In addition, in recent years, traditional Chinese medicines with anti‐inflammatory, immunomodulatory, or cartilage‐protective effects have also been widely used in the treatment of RA (Pu et al, ; Zeng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of traditional Chinese medicines resistant to Bi Zheng show the potentials to treat RA (Gao, Feng, Zhang, Wang, & Cui, ; Zeng et al, ). In addition, in recent years, traditional Chinese medicines with anti‐inflammatory, immunomodulatory, or cartilage‐protective effects have also been widely used in the treatment of RA (Pu et al, ; Zeng et al, ). Therefore, the herbal compounds with anti‐RA activities were reviewed in this paper, and the cheminformatics tools were used to predict their drug‐likeness properties and pharmacokinetic parameters, so as to provide the references for their follow‐up researches and developments.…”
Section: Introductionmentioning
confidence: 99%